Citrinin-producing capacity of Monascus purpureus in response to low −frequency magnetic fields. (February 2017) - Wan, Yunlei; Zhang, Jialan; Han, Hongxia; Li, Li; Liu, Yingbao; Gao, Mengxiang
Graphical abstract: Low-frequency magnetic field (LF-MF) is a preferable way to alter M. purpureus metabolism to reduce citrinin production and to increase pigments and monacolin K production without affecting cell growth. Highlights: Low-frequency magnetic field (LF-MF) inhibited citrinin content by M. purpureus . LF-MF did not affect M. purpureus cell growth when regulating citrinin metabolism. LF-MF increased the production of pigments and monacolin K. Abstract: Citrinin is a type of mycotoxin that negatively affects Monascus products. Application of a low-frequency magnetic field (LF-MF) decreased citrinin production by M. purpureus in liquid-state fermentation during shake flask culture. Under 30 °C incubation, six different magnetic field induction intensity (MF-II), four different exposure times and five exposure time periods were tested to discover optimal treatment conditions. The cultures were exposure to a MF-II of 1.6 mT from 0 to 2 d of incubation time. With LF-MF treatment, peak citrinin production decreased by 46.7% while yellow, red, orange pigments and monacolin K production increased by 31.3%, 40.3%, 41.7% and 29.3%, respectively, compared with control groups at 12 d of incubation. Moreover, the relative expression levels of the citrinin biosynthesis genes pksCT and ctnA were 0.46 and 0.43 times lower, respectively, than the control values relative to the GAPDH reference gene. This study provides evidence that LF-MF is a preferable way to alter M. purpureus metabolism to reduce citrinin production and to increase pigments and monacolin K production without affecting cell growth. Therefore, LF-MF may be used as a tool to process Monascus products to obtain important functional food additive while reducing the adverse effects of citrinin.